Time, uncertainty and knowledge: the foundations and the modernity of Carl Menger's contribution. Issue 5 (3rd September 2022) - Arena, Richard
Abstract: This contribution is dedicated to the originality and the modernity of Carl Menger's contribution today . The focus here is not, however, on defining this originality relative to economists of the past, that is either the so-called "founders" of the "Neo-classical School" (such as Léon Walras or Vilfredo Pareto), or Menger's followers (such as Friedrich von Wieser or Friedrich Hayek). Instead, this contribution focuses the originality and the modernity of Menger's work in relation to the various forms of contemporary economics with a view to investigate the remaining and persistent relevance of Menger's approach for modern economics. Specifically, this paper focuses on three main concepts that express the modernity and originality of Menger's works: time, uncertainty and knowledge. It finally stresses the relation between Menger and modern complexity economics.